Load margin expansion for sustainable power system operation - E.E, Hassan; T.K.A, Rahman; Nazrulazhar, Bahaman; Zuhaina, Zakaria (2018)
An efficient reactive power management is important in providing secured operation for a power system in terms of maintaining its stability condition. Lack of safe operating margin and reactive power support were known to cause a system to operate in an unstable voltage condition. Hence, voltage stability improvement must be planned properly so that the likeliness to instability event could be determined before the more severe event of blackout could occur in a system. For that reason, the application of the developed a new optimization technique namely Adaptive Tumbling Bacterial Foraging (ATBO) was to obtain the most possible optimal Reactive Power Planning (RPP) solution. The objective of RPP problem was not only to minimize the total power losses in a system but was also extended in terms of voltage stability and now termed as security constrained RPP (SCRPP). In order to ensure maximum benefit while ensuring secure operating condition and minimum impact to environment, the proposed ATBFO and Multi objective ATBFO (MOATBFO) were utilized to solve for the single and multi-objective for SCRPP issues. The performance of the proposed techniques were comprehensive analyzed between two other familiar optimization methods known as original Bacterial Foraging Optimization (BFO) algorithm and Meta heuristic Evolutionary Programming (Meta-EP) for standard IEEE 57 bus system. From the results it shows that the multi objective ATBFO optimization is able to give better overall improvement among all objective functions of SCRPP.